2018
DOI: 10.2147/dmso.s169925
|View full text |Cite|
|
Sign up to set email alerts
|

Daily intake of <em>Kaempferia parviflora</em> extract decreases abdominal fat in overweight and preobese subjects: a randomized, double-blind, placebo-controlled clinical study

Abstract: PurposeObesity is a serious problem, which is now a worldwide health problem. Kaempferia parviflora extract (KPE) exhibits anti-obesity effects in animals. However, as no clinical trials have evaluated the anti-obesity effects of KPE in humans, we examined the effects of KPE in reducing abdominal fat in overweight and preobese Japanese subjects.Materials and methodsA 12-week, single-center, randomized, double-blind, placebo-controlled clinical trial was conducted. Seventy-six subjects (males and females aged 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…Clinical trials on the effect of KP in human subjects have also confirmed these findings as observed that a single dose of KP extract capsule affected the enhancement of whole-body energy expenditure and decreased the body fat without effect on food uptake [26]. Moreover, KP extract decreased body weight gain and abdominal fat accumulation in overweight and pre-obese subjects [34]. Taken together, giving the KP extract at both 90 and 180 mg/day doses for 28 days did not affect the blood glucose level under glucose tolerance test in healthy volunteers.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Clinical trials on the effect of KP in human subjects have also confirmed these findings as observed that a single dose of KP extract capsule affected the enhancement of whole-body energy expenditure and decreased the body fat without effect on food uptake [26]. Moreover, KP extract decreased body weight gain and abdominal fat accumulation in overweight and pre-obese subjects [34]. Taken together, giving the KP extract at both 90 and 180 mg/day doses for 28 days did not affect the blood glucose level under glucose tolerance test in healthy volunteers.…”
Section: Discussionmentioning
confidence: 83%
“…Sport supplement formulation containing the combination of KP extract with two other plants also increased physical endurance in healthy volunteers [39]. Considering the clinical effects on physical fitness, promotion of energy expenditure, anti-obesity, and the hyperglycemic effect in an animal model [6,26,33,34], the effect of KP extract on glucose tolerance test at doses of 90 and 180 mg/day for one month consecutive consumption was conducted in healthy volunteers in this study. It is interesting to find that KP extract at doses of 90 and 180 mg/day had no effect on the capacity of the body to manage glycemic condition after the passage of glucose into the human gut and kept the normal limit of blood glucose within 2 h as similarly observed in the placebo group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other reports suggest that oral intake of KPE increases energy expenditure and fat utilization in humans [15,16]. Moreover, dietary intake of KPE reportedly decreases body fat (visceral and subcutaneous fat) in overweight and pre-obese subjects [17]. Collectively, these findings suggest that KPE could be used to reduce body fat in humans.…”
Section: Introductionmentioning
confidence: 70%
“…Moreover, the ethyl acetate extract of K. parviflora also suppressed the glucose and lipid metabolism in Tsumura, Suzuki, Obese Diabetes (TSOD) mice [23,30]. Several clinical trials showed the potential activities of KP extract including increased physical fitness in elderly volunteers and in soccer players [31-4 32], decreased abdominal fat in overweight and pre obese subjects [33], improved selfassessed sex health in men [34] and reduction of stress and anxiety in adult subjects [35].…”
Section: Introductionmentioning
confidence: 99%